2007
DOI: 10.1016/j.ydbio.2007.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary margin transdifferentiation from neural retina is controlled by canonical Wnt signaling

Abstract: The epithelial layers of the ciliary body (CB) and iris are non-neural structures that differentiate from the anterior region of the eyecup, the ciliary margin (CM). We show here that activation of the canonical Wnt signaling pathway is sufficient and necessary for the normal development of anterior eye structures. Pharmacological activation of beta-catenin signaling with lithium (Li(+)) treatment in retinal explants in vitro induced the ectopic expression of the CM markers Otx1 and Msx1. Cre-mediated stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
162
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(180 citation statements)
references
References 68 publications
18
162
0
Order By: Relevance
“…As these studies relied on global overexpression studies, they did not differentiate between proliferation rates in the CMZ vs. the central retina. In contrast, other studies performed in chick and mice describe a reduction in proliferation upon constitutive activation of the Wnt/b-catenin pathway (Cho and Cepko, 2006;Liu et al, 2007). Our results that Wnt/b-catenin pathway activation leads to a loss of cyclinD1 and myca expression accompanied by a loss or reduction in BrdU incorporation is in agreement with these later studies.…”
Section: Developmental Dynamicssupporting
confidence: 93%
See 4 more Smart Citations
“…As these studies relied on global overexpression studies, they did not differentiate between proliferation rates in the CMZ vs. the central retina. In contrast, other studies performed in chick and mice describe a reduction in proliferation upon constitutive activation of the Wnt/b-catenin pathway (Cho and Cepko, 2006;Liu et al, 2007). Our results that Wnt/b-catenin pathway activation leads to a loss of cyclinD1 and myca expression accompanied by a loss or reduction in BrdU incorporation is in agreement with these later studies.…”
Section: Developmental Dynamicssupporting
confidence: 93%
“…In mouse and chick, constitutive activation of the Wnt/b-catenin pathway causes expansion of the ciliary body and iris demonstrating that Wnt/ b-catenin signaling is required for the induction of peripheral fates (Cho and Cepko, 2006;Liu et al, 2007;Kubo and Nakagawa, 2009). We observed that in zebrafish ectopic expression of Wnt target genes leads to the upregulation and expansion of otx1, a marker for the future ciliary epithelium and iris in mice that is normally expressed in the distal tip of the eye …”
Section: Wnt/b-catenin Signaling Up-regulates Peripheral Fate/ Stem Cmentioning
confidence: 99%
See 3 more Smart Citations